Oeis Syndrome (Cloacal Exstrophy): About Two Cases Treated at the Mother and Child Teaching Hospital in Cotonou (Benin) - GBENOU, ANTOINE SÉRAPHIN; Akodjenou, Joseph; TCHIAKPE-ENIALOKO, NICOLE; FIOGBE, ARMAND MICHEL (My University, 2020)
Introduction: OEIS syndrome, the most severe form of exstrophy-epispadias complex, is characterized by the existence of an omphalocele, a bladder exstrophy, an anal imperforation and a spina bifida. Case Presentation: Two clinical cases admitted at the first day of life in neonatology department are reported; one was born by caesarean section, weighing 2500 g and the other one vaginally with a weight at 1890 g. The first child’s mother was a primigravid, primiparous and the second mother was multiparous. Prenatal ultrasound was performed in one case. The clinical examination found two exstrophied hemi-bladders with two productive ureteral meatus, separated by a double intestinal orifice, a manifestation of anal imperforation, omphalocele, spina bifida and lumbar vertebral malformations; which corresponds to a typical form of OEIS syndrome. One of the babies had an associated clubfoot. The karyotype could not be performed. Both were dead; the first in the early postoperative period, the second one at 16 days of life without surgery. Conclusion: OEIS syndrome is a rare condition and represents a therapeutic challenge in developing countries. Promoting prenatal diagnosis is essential.
Keywords: OEIS Syndrome; Cloacal Exstrophy; Newborn; Prenatal Diagnosis